2021
DOI: 10.3390/rs13234741
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Groundwater-Induced Subsidence for London and Delhi Using PSInSAR

Abstract: Groundwater variation can cause land-surface movement, which in turn can cause significant and recurrent harm to infrastructure and the water storage capacity of aquifers. The capital cities in the England (London) and India (Delhi) are witnessing an ever-increasing population that has resulted in excess pressure on groundwater resources. Thus, monitoring groundwater-induced land movement in both these cities is very important in terms of understanding the risk posed to assets. Here, Sentinel-1 C-band radar im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Bear et al 96 used the mathematical model for regional land subsidence due to pumping groundwater. Agarwal et al 97 depict the comparative study of groundwater-induced subsidence for London and Delhi Using PS-InSAR, which is based on the mathematical model. Khorrmi et al 1 used the Piezometric data and found the extreme subsidence in a populated city (Mashhad) detected by PS-InSAR considering groundwater withdrawal and geotechnical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Bear et al 96 used the mathematical model for regional land subsidence due to pumping groundwater. Agarwal et al 97 depict the comparative study of groundwater-induced subsidence for London and Delhi Using PS-InSAR, which is based on the mathematical model. Khorrmi et al 1 used the Piezometric data and found the extreme subsidence in a populated city (Mashhad) detected by PS-InSAR considering groundwater withdrawal and geotechnical properties.…”
Section: Resultsmentioning
confidence: 99%
“…These results confirm that 70% of the rain that falls is channeled into surface runoff, while 30% is lost due to infiltration and evapotranspiration processes, thus potentially causing inundation and urban flooding. Furthermore, urban flooding is influenced by several factors, namely the drainage system, runoff coefficient and land elevation [60]. The facts found indicate that changes in land use have an influence on changes in the hydrological cycle, damage to natural vegetation and changes in forest cover.…”
Section: Fig6 (A-c) Carrying Capacity Of Land and Carrying Capacity Of Water Resources (A) Land Cover Index; (B) Availability Of Water; (mentioning
confidence: 99%
“…These images provide a valuable visual indicator of the presence of rock glaciers. Remote sensing data enables easy and comprehensive surveying of challenging terrains, covering vast spatiotemporal scales (Agarwal, 2022;Agarwal et al, 2021Agarwal et al, , 2023Qin et al, 2021). Satellite imagery allows for the identification of geomorphological features such as ridge and furrow topography (Kääb & Weber, 2004), ice content, and surface characteristics that distinguish active and relic rock glaciers.…”
Section: Remote Sensing Datamentioning
confidence: 99%